2020
DOI: 10.3389/fpsyt.2020.553463
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing a Decade of Research Into Suicide and Related Behaviour Using the South London and Maudsley NHS Foundation Trust Clinical Record Interactive Search (CRIS) System

Abstract: Suicide is a serious public health issue worldwide, yet current clinical methods for assessing a person's risk of taking their own life remain unreliable and new methods for assessing suicide risk are being explored. The widespread adoption of electronic health records (EHRs) has opened up new possibilities for epidemiological studies of suicide and related behaviour amongst those receiving healthcare. These types of records capture valuable information entered by healthcare practitioners at the point of care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…With the power of increased computational modeling, in addition to single words, (a) multi-word "phrases" and (b) multiword/phrase "topics" can be extracted and used to improve language models that capture personality (Eichstaedt et al, 2020). Mining of electronic health records has also been used to provide large samples of textual language to assess mental health (Bittar et al, 2020;Boag et al, 2021). However, to date few studies have applied these techniques to spoken language, especially with patients, which provides unique challenges to obtain, but exciting opportunities for improving language models used to capture psychiatric constructs.…”
Section: Incremental Validity Of Language-based Assessments Of Person...mentioning
confidence: 99%
“…With the power of increased computational modeling, in addition to single words, (a) multi-word "phrases" and (b) multiword/phrase "topics" can be extracted and used to improve language models that capture personality (Eichstaedt et al, 2020). Mining of electronic health records has also been used to provide large samples of textual language to assess mental health (Bittar et al, 2020;Boag et al, 2021). However, to date few studies have applied these techniques to spoken language, especially with patients, which provides unique challenges to obtain, but exciting opportunities for improving language models used to capture psychiatric constructs.…”
Section: Incremental Validity Of Language-based Assessments Of Person...mentioning
confidence: 99%
“…First, although some projects have already demonstrated that NLP algorithms applied on clinical reports could extract variables of interest regarding mental health 23 – 27 , many of these algorithms were developed using disease-, age- or hospital-specific cohorts and concerns have been raised regarding their generalisability 28 . It is therefore necessary to train and validate NLP algorithms on datasets that are representative of various contexts of care to detect indications on mental health that are often scattered among millions of reports edited throughout care organisations.…”
Section: Introductionmentioning
confidence: 99%